Quantitative Proteomics Reveals a Role for SERINE/ARGININE-Rich 45 in Regulating RNA Metabolism and Modulating Transcriptional Suppression via the ASAP Complex in Arabidopsis thaliana - Chen, Samuel L.; Rooney, Timothy J.; Hu, Anna R.; Beard, Hunter S.; Garrett, Wesley M.; Mangalath, Leann M.; Powers, Jordan J.; Cooper, Bret; Zhang, Xiao-Ning (Frontiers in Plant Science, 2019)
Pre-mRNA alternative splicing is a conserved mechanism for eukaryotic cells to leverage existing genetic resources to create a diverse pool of protein products. It is regulated in coordination with other events in RNA metabolism such as transcription, polyadenylation, RNA transport, and nonsense-mediated decay via protein networks. SERINE/ARGININE-RICH 45 (SR45) is thought to be a neutral splicing regulator. It is orthologous to a component of the apoptosis and splicing-associated protein (ASAP) complex functioning to regulate RNA metabolism at multiple levels. Within this context, we try to understand why the sr45-1 mutant Arabidopsis has malformed flowers, delayed flowering time, and increased disease resistance. Prior studies revealed increased expression for some disease resistance genes and the flowering suppressor Flowering Locus C (FLC) in sr45-1 mutants and a physical association between SR45 and reproductive process-related RNAs. Here, we used Tandem Mass Tag-based quantitative mass spectrometry to compare the protein abundance from inflorescence between Arabidopsis wild-type (Col-0) and sr45-1 mutant plants. A total of 7,206 proteins were quantified, of which 227 proteins exhibited significantly different accumulation. Only a small percentage of these proteins overlapped with the dataset of RNAs with altered expression. The proteomics results revealed that the sr45-1 mutant had increased amounts of enzymes for glucosinolate biosynthesis which are important for disease resistance. Furthermore, the mutant inflorescence had a drastically reduced amount of the Sin3-associated protein 18 (SAP18), a second ASAP complex component, despite no significant reduction in SAP18 RNA. The third ASAP component protein, ACINUS, also had lower abundance without significant RNA changes in the sr45-1 mutant. To test the effect of SR45 on SAP18, a SAP18-GFP fusion protein was overproduced in transgenic Arabidopsis Col-0 and sr45-1 plants. SAP18-GFP has less accumulation in the nucleus, the site of activity for the ASAP complex, without SR45. Furthermore, transgenic sr45-1 mutants overproducing SAP18-GFP expressed even more FLC and had a more severe flowering delay than non-transgenic sr45-1 mutants. These results suggest that SR45 is required to maintain the wild-type level of SAP18 protein accumulation in the nucleus and that FLC-regulated flowering time is regulated by the correct expression and localization of the ASAP complex.